COMPUTATIONS OF EVAPORATION FROM WATERSHEDS OF NORTH-WESTERN RUSSIA - Сало, Юрий Андреевич; Назарова, Лариса Евгеньевна; Балаганский, Андрей Федорович; Salo, Yuri; Nazarova, Larisa; Balagansky, Andrey (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2016)
The paper presents a comparison between the results of calculations of the potential rate of evaporation and gross evaporation from watersheds of Northwest Russia with some best known dependencies developed by different authors. It is demonstrated that the best results are achieved using the formulae developed by Oldekop and Schreiber, where normal potential rates of evaporation are calculated with a regression obtained by Yu. A. Salo. A model for estimating runoff from hydrologically understudied watersheds based on observed data on air temperature and atmospheric precipitation is proposed.